Effectiveness of Literacy Program in Primary Education - Ariyani, Windya Retno; Marmoah, Sri; Winarno, Winarno (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to evaluate the effectiveness of the School Literacy Movement (GLS) in shaping students' reading habits and literacy culture in primary education, particularly in rural elementary schools. Methodology: A qualitative evaluation approach was used, adopting the Kaufman five-level evaluation model. Data were gathered through observation, structured interviews, and documentation across six elementary schools in the Sudirman cluster, Wonogiri District, using triangulation and interactive data analysis. Main Findings: The study finds that the effectiveness of GLS implementation is closely linked to leadership commitment, teacher involvement, student participation, and documentation systems. Schools with structured routines, contextual innovation, and community support show stronger outcomes in reading habits, student expression, and collaborative literacy culture. Novelty/Originality of this study: This study uniquely applies Kaufman's evaluation model in a rural education setting, capturing not only program performance but also the integration of literacy into school routines and culture. It presents a contextualized analysis of GLS, offering a practical framework for policy refinement and school-based literacy development.